En artificiellt intelligent inre marknad: En analys av den föreslagna AI-förordningen och dess betydelse för säkerställandet av en väl fungerande inre marknad för AI - Sedvall,Fredrik (2023)
In recent years, significant technological advancements have been made in the field of artificial intelligence (AI). AI is a complex technical domain that involves the development of software and hardware capable of mimicking the cognitive abilities normally associated with humans. Technological advancements in AI are expected to bring about substantial economic and social benefits. However, these advancements do not come without risks. Against the backdrop of an ongoing digital transformation of the European Union’s (EU) single market, the EU has recognized the need of a more uniform regulatory framework for AI. Hence, in 2021, the European Commission introduced a proposal for a regulation laying down harmonized rules for AI (the AI Act). The primary objective of the regulation is to ensure the proper functioning of the single market by creating the conditions for the development and use of trustworthy AI in the Union. The AI Act sets forth comprehensive requirements for providers of AI systems, based on an assessment of the AI system’s level of risk. Additionally, the regulation introduces measures aimed at fostering innovation. Considering the EU’s objectives for the single market, this thesis examines the provisions of the AI Act, with the aim of investigating what constitutes a proper functioning single market for AI, and to what extent the AI Act ensures such a market. The analysis is based on the underlying premise that the freedom to conduct a business, enshrined in the EU’s Charter of Fundamental Rights, plays an important role in facilitating a proper functioning single market. Moreover, the thesis presents a market liberal perspective on the freedom to conduct a business. The thesis concludes that a proper functioning single market for AI particularly relies on favorable conditions for innovation and investment. Furthermore, it is argued that the AI Act does not ensure this, due to the extensive, costly, and burdensome requirements it lays out for providers of AI systems, coupled with inadequate measures to foster innovation. Consequently, it risks undermining the broader objectives of the regulation, and have adverse effects on the EU’s global competitiveness in the field of AI.
Keywords: EU-rätt; IT-rätt; AI-förordning; Inre marknad; Näringsfrihet